Kerkwees in die voetspore van Christus volgens Efesiërs 4 en 5 - Dreyer, Wim A. (2017)
This contribution contains a sermon delivered as opening address to the 71st General Assembly of the Nederduitsch Hervormde Kerk van Afrika (NHKA). For the last twenty years the NHKA had been involved in a process of ecclesial transformation, based on fundamental shifts in ecclesiology. This opening address reflects on the nature and calling of the church in light of Ephesians 4 and 5, with the specific focus on ‘being church in the footsteps of Christ’. Much emphasis is placed on the verb ‘peripateo’ which appears five times in these two chapters. It is suggested that it could be translated as ‘following in the footsteps of someone’ and that this has very specific implications for being church in the 21st century. Ephesians 4 and 5 articulate being church in the footsteps of Christ in terms of unity, holiness, love, light and wisdom.
Keywords: Sociology and Ethics; Ancient Semitic and Classical Languages; Philosophy; Aspects of Religious Studies; Practical Theology; Ministers of Religion; Scholars; Philosophers; Theologians; Netherdutch Reformed Church; Theology